Dynamic observation of IL-33 and its receptors in HIV patients who received HAART - He, B.; Zheng, L.; Zhou, H.; He, Y.; Chen, Z.; Xiao, S.; Wang, H.; Ling, Y.; Zheng, Y. (Cellular and Molecular Biology, 2017)
The purpose of this study was to observe the changes in serum IL-33 and its soluble receptors, serum sST2 level and ST2L expression in PBMCs of HIV-infected patients receiving highly-active antiretroviral therapy (HAART) for 12 monthes. Fifty-five chronic HIV-1-infected adults were recruited for this study before initiation of HAART. 30 age and gender matched healthy adults were recruited as control. Blood was obtained from each patient at baseline (0 month) and 12 months after initiation of highly active antiretroviral therapy(HAART), and each healthy person. The concentration of serum IL-33 and sST2 were detected by ELISA. plasma HIV RNA was detected by real-time fluorescent quantitative PCR. peripheral blood CD3+/CD4+ cell count, the ratio of CD4+ST2L+ positive peripheral blood mononuclear cells (PBMCs) were determined by flow cytometry. In HIV-infected patients, serum IL-33 and sST2 levels are higher and percentage of ST2L in PBMCs is lower than normal control significantly. During HAART, serum IL-33 and sST2 levels were decreased, whereas CD4+ST2L+ level was increased in PBMCs gradually. Serum IL-33 and sST2 levels positively correlated with plasma HIV RNA levels, but negatively correlated with the peripheral blood CD3+/CD4+ cell count. CD4+ST2L+ receptor in PBMC are positively correlated with the peripheral blood CD3+/CD4+ cell count, but negatively correlated with the plasma HIV viral loading. Serum IL-33 and sST2 levels, and CD4+ST2L+ expression in PBMCs are closely associated with HIV-1 infection and immune reconstitution in patients received HAART.